2014
DOI: 10.1039/c4an00750f
|View full text |Cite
|
Sign up to set email alerts
|

Magnetite-doped polydimethylsiloxane (PDMS) for phosphopeptide enrichment

Abstract: Reversible phosphorylation plays a key role in numerous biological processes. Mass spectrometry-based approaches are commonly used to analyze protein phosphorylation, but such analysis is challenging, largely due to the low phosphorylation stoichiometry. Hence, a number of phosphopeptide enrichment strategies have been developed, including metal oxide affinity chromatography (MOAC). Here, we describe a new material for performing MOAC that employs a magnetite-doped polydimethylsiloxane (PDMS), that is suitable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…In summary, the on‐chip magnetic SPE‐MALDI‐TOF MS system with In 2 O 3 ‐coated Fe 3 O 4 MNPs as the adsorbent led to high selectivity, good reusability, and low detection limit when used for the detection of phosphopeptides. In addition, a comparison of the present system with some reported methods employing various magnetic metal oxides revealed that the present approach provided comparable selectivity, sensitivity, rapidness, and reagent dosage [, ].…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In summary, the on‐chip magnetic SPE‐MALDI‐TOF MS system with In 2 O 3 ‐coated Fe 3 O 4 MNPs as the adsorbent led to high selectivity, good reusability, and low detection limit when used for the detection of phosphopeptides. In addition, a comparison of the present system with some reported methods employing various magnetic metal oxides revealed that the present approach provided comparable selectivity, sensitivity, rapidness, and reagent dosage [, ].…”
Section: Resultsmentioning
confidence: 94%
“…Miniaturized total analysis system integrates many sample‐handling steps into a microchip with micrometer scale and has the advantages of reducing reagent wastage, shortening analysis time, and controlling liquid flow, which makes it receive universal attention in many fields . At present, extraction materials for SPE in microchips consist of membranes, polymer monoliths, and magnetic nanoparticles (MNPs) .…”
Section: Introductionmentioning
confidence: 99%
“…Test materials were then etched, using a previously reported etchant solution for PDMS [35], to remove surface elastomer and expose the underlying nanoparticles, whilst control samples remained unetched. This method enables straightforward production of functional materials in a manner that can readily be customised (for example altering dopant materials and concentrations) and can be combined with other fabrication techniques, such as replica moulding [30] and extrusion, to produce medical devices.…”
Section: Resultsmentioning
confidence: 99%
“…However, when bulk doping polymers, the nanoparticles become embedded within the polymer matrix. Etching back the surface matrix can expose the underlying nanoparticles [30], simultaneously producing a roughened surface with high surface area (favourable to photocatalysis). This would allow for closer contact between the photoactive TiO 2 and attached bacteria, potentially increasing cytotoxic ROS exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Bruening et al reported TiO 2 nanoparticles-decorated porous nylon membrane for rapid phosphopeptide enrichment . Moreover, magnetite-doped polydimethylsiloxane and microfluidic devices supporting TiO 2 nanotube array or TiO 2 –ZrO 2 have also been designed for efficient on-chip enrichment of phosphopeptides through a rapid and straightforward protocol. The microfluidic device supporting TiO 2 nanotube array, for example, realized the efficient enrichment of serum phosphopeptide, which proved the differential expression of serum phosphopeptides between ovarian cancer patients and healthy women.…”
Section: Affinity Materials For the Enrichment Of Phosphorylated Prot...mentioning
confidence: 99%